First evaluation of bendiocarb in experimental huts using different substrates in Madagascar. (December 2016) - Randriamaherijaona, Sanjiarizaha; Nepomichene, Thiery; Assoukpa, Jade; Madec, Yoann; Boyer, Sébastien
Abstract Background Indoor residual spraying with insecticide is recommended for malaria control in high-transmission settings. Determination of residual activity of insecticides is essential for the selection of appropriate indoor spraying policy. The present study was undertaken to evaluate the residual effect of bendiocarb, a carbamate insecticide used in Madagascar, on different indoor surfaces in order to elaborate future vector control interventions. Methods The residual activity of bendiocarb was evaluated in both experimental huts and houses. Tests in experimental huts on different substrates represented a small scale-field trials. The houses IRS performed in parallel of experimental huts IRS, was done to compare semi-field results and field results. Bioassays according to the World Health Organization (WHO) standard protocol were carried out on different substrates impregnated with bendiocarb using susceptible strains ofAnopheles arabiensis andAedes albopictus . Results Bendiocarb induced significantly high mortality in treated huts against exposed mosquito (p < 0.005) compared to untreated huts. The mortality is up to the WHO threshold of 80 % during 5 months post-treatment. Using a multivariate analysis, Ae. albopictus mortality decreased significantly from the 3rd month post-treatment. However, An. arabiensis mortality decreased significantly from the 4th month after treatment. Comparing mosquito mortality results from the mud experimental huts and the mud houses showed no significant difference regarding the persistence of bendiocarb on wall. Conclusions Current data suggest variable persistence of bendiocarb according to the type of wall surfaces, highlighting the importance of testing insecticide for IRS in local context before using them in large scale. Data from this study validate also the importance of using experimental huts as representative tool to evaluate the effectiveness of an insecticide.